Endoscopic Thyroidectomy Using the Unilateral Axillo-breast Approach Versus the Modified Anterior Chest Wall Approach: A Prospective Comparative Study. Issue 6 (December 2018) - Elzahaby, Islam A.; Fathi, Adel; Abdelwahab, Khaled; Eldamshiety, Osama; Metwally, Islam H.; Abdallah, Ahmed; Ramadan, Mohamed M.; Kotb, Sherif; Abdel Aziz, Mahmoud; Refky, Basel; Abouzid, Amr; Saleh, Saleh; et al.
Abstract : Introduction: Endoscopic thyroidectomy (ET) has become a well-established surgical technique that is mainly performed for benign thyroid lesions. Several endoscopic approaches are available, such as transaxillary, unilateral axillo-breast approach (UABA), modified anterior chest wall approach (MACWA), bilateral axillo-breast approach, and most recently the transoral approach and the robotic-assisted techniques. There is no recommended approach, because each approach has its own positive and negative attributes. We, herein, compare between UABA and MACWA in terms of surgical and cosmetic outcomes. Methods: This prospective study was conducted from April 2016 to August 2017. Forty patients with unilateral benign thyroid lesions were selected. Of them, 20 patients underwent ET using UABA, and 20 patients underwent ET using MACWA. Gas insufflation was implemented for all patients. Clinicopathologic data, surgical outcomes, and cosmetic outcomes in both groups were analyzed. Results: There was no significant difference between both groups in the clinicopathologic characteristics. The mean surgical time was significantly longer in the UABA group compared with the chest wall group (147.3 vs. 124.3 min). The postoperative pain scores were relatively lower in the UABA group compared with the MACWA group. We reported a higher rate of persistent paresthesia, neck contracture with swallowing discomfort, and hypertrophic scars in the MACWA group. Cosmetic satisfaction scores for patients who underwent UABA were higher than for those who underwent MACWA. Conclusions: Both approaches were similar in terms of safety, feasibility, and operative complications. Even though the surgical time was longer, patients who underwent the UABA reported relatively less postoperative pain, superior cosmetic results, scar perception, and patient satisfaction compared with MACWA.